COMPETITIVENESS OF THE ENTERPRISE IN THE CONDITIONS OF THE DIGITAL ECONOMY - TKACHENKO, IVAN; SHARKO, VITALII (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The paper analyzes the methods and main stages of digitization of business processes of an industrial enterprise. The main segments of the digital economy have been identified and the conceptual strategic map of an industrial enterprise has been improved. The authors found that digitalization has the greatest impact on such components of business processes of industrial enterprises as: interaction with customers, cost and internal infrastructure management. Digitalization of industry is an integral part of the National Economic Strategy. This requires the tran-formation of traditional business processes of industrial enterprises, analysis of the components of digitalization, determining the stages of its implementation, development of recommendations for planning and systematization of digitalization processes. Purpose. Identify and describe the elements of digitalization of business processes of industrial enterprises, methods and procedure for implementing digitalization measures in modern conditions, to develop successive stages of business process transformation, to propose a method that will allow to systematize measures for business process transformation. Research methods. In the process of research the economic method was used to study the trends of industry digitalization, the method of system analysis was used to identify the struc tural elements of the digitization of business processes. We used methods of comparison, analogy and systematization, a comprehensive review of academic literature. Research results. The main elements of digital transformations are considered: work with clients, operational business processes and business models of the enterprise and their characteristic is resulted. The methods and main stages of digitalization of business processes of an industrial enterprise are analyzed. It is determined that the methodology of digitalization of business processes of the enterprise is based on the basic concepts of information systems that have evolved. Digitalization has the greatest impact on such components of business processes as: interaction with customers, value proposition and internal infrastructure management. The most common elements of the integrated information environment used by industrial enterprises to automate all business processes are described. Recommendations. The practical value of the article is to structure the elements of business digitalization, which will allow companies to systematically approach the transformation of business processes. Industrial enterprises are invited to develop maps of digital transformations, which will allow concentrating resources on the most promising areas of development.